Reduction of Pseudo-geminal Bis(ethynyl)-Substituted [2.2]Paracyclophanes - Sarbu, Laura G.; Hopf, Henning; Grunenberg, Jörg; Birsa, Lucian M. (Synlett, 2015)
The reduction of pseudo-geminal bis(ethynyl)-substituted [2.2]paracyclophanes provides compounds with new bridges. The type of bridging is substituent dependent. The (trimethylsilyl)ethynyl moiety induces the formation of a bridge with two semicyclic double bonds; less bulky substituents, like propynyl and phenylethynyl, lead to bridges with endo double bonds.
Keywords: acetylenes; reduction; dienes; lithium; paracyclophanes